2017
DOI: 10.1101/gr.218032.116
|View full text |Cite
|
Sign up to set email alerts
|

The Mobile Element Locator Tool (MELT): population-scale mobile element discovery and biology

Abstract: Mobile element insertions (MEIs) represent ∼25% of all structural variants in human genomes. Moreover, when they disrupt genes, MEIs can influence human traits and diseases. Therefore, MEIs should be fully discovered along with other forms of genetic variation in whole genome sequencing (WGS) projects involving population genetics, human diseases, and clinical genomics. Here, we describe the Mobile Element Locator Tool (MELT), which was developed as part of the 1000 Genomes Project to perform MEI discovery on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
434
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 320 publications
(477 citation statements)
references
References 88 publications
38
434
5
Order By: Relevance
“…Among these, one insertion originated from a donor L1 on Chromosome 22 previously found to be responsible for tumor-specific L1 insertions in other human cancer types (Pitkanen et al 2014;Tubio et al 2014;Paterson et al 2015). An increasing body of evidence suggests that a particular subset of retrotransposition-competent L1 loci tend to be recurrent contributors to genomic instability in human malignancies and cancer cell lines (Tubio et al 2014;Philippe et al 2016;Scott et al 2016;Gardner et al 2017). Indeed, here we found that the promoter region of the TTC28 donor L1 was largely demethylated in both nontumor liver and matched ICC tumor cells, as a prior study found for a Chromosome 17 donor L1 responsible for APC exon mutagenesis in a colorectal cancer patient (Scott et al 2016).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Among these, one insertion originated from a donor L1 on Chromosome 22 previously found to be responsible for tumor-specific L1 insertions in other human cancer types (Pitkanen et al 2014;Tubio et al 2014;Paterson et al 2015). An increasing body of evidence suggests that a particular subset of retrotransposition-competent L1 loci tend to be recurrent contributors to genomic instability in human malignancies and cancer cell lines (Tubio et al 2014;Philippe et al 2016;Scott et al 2016;Gardner et al 2017). Indeed, here we found that the promoter region of the TTC28 donor L1 was largely demethylated in both nontumor liver and matched ICC tumor cells, as a prior study found for a Chromosome 17 donor L1 responsible for APC exon mutagenesis in a colorectal cancer patient (Scott et al 2016).…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, the finding that Mdr2 −/− mice accommodate tumor-specific L1 retrotransposition is particularly interesting, as these genomic alterations occur alongside massive gene amplifications (Iannelli et al 2014). All four tumor-specific mouse L1 insertions were full-length and therefore likely to retain retrotransposition competence, allowing them to serve as potential donor L1s for subsequent tumor-specific retrotransposition events, as previously observed in human malignancies (Tubio et al 2014;Gardner et al 2017).…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations